DEVELOPMENT OF TOURISM AND RELIGIOUS VILLAGES IN SUMBERRANTAS VILLAGE, BATU CITY - Mujtahid; Dini Sadiyah; Muhammad Ma'ruf; Falah Al-Amin; Farhan Hidayat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the development and expansion of tourism and religious villages in Sumberbrantas Village, Batu City, and their impact on the local community. Sumberbrantas Village boasts pristine mountainous natural beauty, a harmonious social life, and strong religious values, offering the potential for development as a community-based tourism and religious village. This study employed a qualitative approach with a descriptive approach. Data collection techniques included observation, in-depth interviews, and documentation, involving village officials, religious leaders, tourism managers, and the local community. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the development of tourism and religious villages in Sumberbrantas Village has had a positive impact on improving the community's economy, preserving socio-cultural and religious values, and increasing public awareness of environmental sustainability. Active community participation and support from the village and regional governments are key contributing factors to the success of tourism and religious village development. However, constraints remain, including limited human resources and suboptimal tourism promotion. Therefore, a well-planned development strategy, community capacity building, and strengthening cooperation between stakeholders are needed to realize a sustainable tourism and religious village.